In vitro P-glycoprotein interactions and steady-state pharmacokinetic interactions between tolvaptan and digoxin in healthy subjects - Shoaf, Susan E; Ohzone, Yoshihiro; Ninomiya, Shin-ichi; Furukawa, Masayuki; Bricmont, Patricia; Kashiyama, Eiji; Mallikaarjun, Suresh (Journal of clinical pharmacology, 2011)
Interactions between tolvaptan and digoxin were determined in an open-label, sequential study where 14 healthy subjects received tolvaptan 60 mg once daily (QD) on days 1 and 12 to 16 and digoxin 0.25 mg QD on days 5 to 16. Mean maximal concentrations (C(max)) and area under the curve during the dosing interval (AUC(τ)) for digoxin with tolvaptan (day 16) were increased 1.27- and 1.18-fold compared with digoxin alone (day 11); mean renal clearance of digoxin was decreased by 59% (P < .05). Tolvaptan C(max) and AUC(0-24h) for a single dose with digoxin (day 12) were each increased about 10% compared with tolvaptan alone (day 1). Tolvaptan did not accumulate upon multiple dosing. After a single dose of tolvaptan (day 1, day 12), 24-hour urine volume was about 7.5 L. As expected, after 5 days of tolvaptan, 24-hour urine volume decreased about 20%. In vitro studies in control and MDR1-expressing LLC-PK1 cells indicate that tolvaptan is a substrate of P-glycoprotein. Tolvaptan (50 µM) inhibited basolateral to apical digoxin secretion to the same extent as 30 µM verapamil; the IC50 of tolvaptan was determined to be 15.9 µM. The increase in steady-state digoxin concentrations is likely mediated by tolvaptan inhibition of digoxin secretion.